Hercules Dome Ice-Penetrating Radar Swath Topographies - Christianson, Knut; Hoffman, Andrew; Holschuh, Nicholas; Paden, John (IEDA: US Antarctic Program Data Center, 2023)
This dataset consists of gridded basal topographies in the vicinity of Hercules Dome, East Antarctica generated from multi-element ice-penetrating radar data.